The role of commercial banks in developing foreign trade techniques in Algeria - Razika, Abdelli; Saida, Ilifi (International journal of economic perspectives, 2024)
Commercial banks play a fundamental role in global economies, extending beyond merely being a source of financing to become a vital component in the process of economic development. The presence of an advanced banking system is essential due to the central role banks play in financial intermediation and providing funding. They significantly contribute to stimulating foreign trade in any country, including Algeria. In Algeria, the importance of commercial banks is evident through their support for developmental projects, services, and infrastructure. These banks also play a crucial role in supporting and developing foreign trade technologies through e-commerce and financing import and export operations. By utilizing their banking and financial tools, commercial banks contribute to enhancing economic development and attracting investments, thereby supporting the growth of the national economy.